Analytical determination of absolute deformations and boundaries of the contact zone of a deformable wheel with a deformable surface - Kovbasa, Volodymyr; Priliepo, Nataliia (Technology audit and production reserves, 2025)
The object of research is the contact interaction between a deformable wheel (tire) and a deformable supporting surface. One of the most problematic areas is defining the boundaries of the contact zone as a function of applied loads, wheel geometry, and the mechanical properties of the contacting surfaces, as well as the increasing need to reduce energy consumption and soil compaction in the context of vehicle running gear systems. During the research, methods from the mechanics of continuous deformable media were used to identify the deformable properties of contacting surfaces. The investigations were founded on previously published research concerning the distribution of contact forces, obtained using biharmonic potential analytical functions based on methods employed by Boussinesq and Cerruti. Analytical dependencies have been derived that relate the leading and trailing edges of the deformable wheel’s (tire’s) contact with the deformable surface. This is because the proposed approach, which considers the relationship between forces and displacements on the surface and deformations and stresses within the contacting bodies, taking into account their mechanical properties, is more informative compared to methods of theoretical and analytical mechanics. The research revealed that the potential for improving the object’s functioning lies in optimizing the selection of parameters and operating modes for running gear systems. Thanks to this, it becomes possible to obtain optimized values for the geometric size of the contact surface. Compared to analogous known approaches, this ensures an enhancement in the tractive efficiency of driving wheels, minimizing wheel slip to acceptable levels, which directly addresses key challenges in agricultural and off-road machinery by contributing to reduced energy consumption and soil compaction.